Masters’ Readiness Formation to Ensuring the Educational Process Quality in the Preschool Educational Institutions in the Process of Professional Disciplines Studying - Liudmula Zahorodnia (Pedagogical Discourse, 2019)
Integration of Ukraine into the European educational space actualizes the issue of education quality ensuring at all educational levels, including the preschool education Masters’ training to the effective educational process management in preschool educational institutions. Purpose. To emphasize the opportunities of professional standard and selective disciplines using in the process of «Preschool Education» specialty Masters’ training to the effective educational process management in preschool educational institutions. Methods. In order to achieve the above pointed goals and objectives, we used the following methods: theoretical – analysis and synthesis of scientific literature and methodological publications; meaningful analysis of Master’s plans, work programmes of professional normative disciplines and selective disciplines; comparison, synthesis, systematization and generalization of the received information.Results. The content of such disciplines has been analysed: «Pedagogy: High School Pedagogy, Education Management, Distance Education», «Theory and Technology of Children’s Creativity Development», «Methodics of the Work Management over Speech Competence Building», «Methodics of Preschoolers’ Mathematical and Logical Development Management», «Technology of Preschoolers’ Environmental Culture Formation», «Current Issues of Researches in Preschool Pedagogy», «Modern Technologies of Health Preservation in Preschool Education». A number of topics and issues has been proposed, the inclusion of which into the professional disciplines content, will improve the process of Masters’ readiness formation to ensure the educational process quality in the preschool educational institutions. The characteristics of pedagogical conditions, compliance of which will ensure the success in the process of Masters’ readiness formation to ensure the educational process quality in the preschool educational institutions has been offered. It is necessary to form the readiness of future Masters to ensure the educational process quality in the preschool educational institutions at the stage of professional training. At the same time, the normative and selective disciplines of the curriculum with relevant topics and issues should be enriched, and their teaching should be carried out in compliance with a number of pedagogical conditions.